Real-world glycemic, blood pressure, and weight control in patients with type 2 diabetes mellitus treated with canagliflozin—an electronic health-record-based study. (2nd June 2016) - Lefebvre, Patrick; Pilon, Dominic; Robitaille, Marie-Noëlle; Lafeuille, Marie-Hélène; Chow, Wing; Pfeifer, Michael; Duh, Mei Sheng
Abstract: Background: Canagliflozin (CANA) has been shown to improve HbA1c, blood pressure (BP), and weight in patients with type 2 diabetes mellitus (T2DM) in clinical trials. This study describes HbA1c, BP, and weight in T2DM patients treated with CANA in a real-world setting. Methods: Adults with ≥1 diagnosis for T2DM and ≥12 months of clinical activity before the first CANA prescription (index) were identified in the IMS Health Real-World Data Electronic Medical Records - US database. Patient quality measures were described at baseline and 3, 6, 9, and 12 months post-index. Selected goals were HbA1c <7% (<53 mmol/mol), <8% (<64 mmol/mol), and >9% (>75 mmol/mol, poor control), BP <140/90 mmHg, and weight loss ≥5%. Results: In total, 16, 163 patients were identified (mean age = 58.5 years; 47.9% female; 75.8% white). At baseline, 90.4% of patients used ≥1 anti-hyperglycemic agent. Among patients with baseline HbA1c ≥7% ( n = 10, 478; 64.8%; mean HbA1c = 8.8%), 21.2%, 59.5%, and 17.6% had an HbA1c <7%, <8%, and >9% after 3 months, respectively; these proportions remained stable through 12 months. Among patients with baseline BP ≥140/90, 60.0% and 75.6% attained systolic BP <140 mmHg and diastolic BP <90 mmHg after 3 months, respectively; proportions remained stable through 12 months. Weight loss ≥5% was observed in 13.3% of patients at 3 months and the proportion increased to 25.8% at 12 months. Limitations: This study relied on prescription data, which does not necessarily indicate that the medication was taken as prescribed. Some patients were also treated with other anti-hyperglycemics, anti-hypertensives, and weight loss medications during the follow-up, which may have contributed to the effects reported. Conclusions: Most patients with inadequate HbA1c and BP levels at baseline achieved respective goals after 3 months of CANA, and the proportions of responders remained stable through 12 months. Weight loss ≥5% was increasingly observed over time.